Motivasi Kerja terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kota Depok - Wiwik Widiyanti (Universitas Bina Sarana Informatika, 2017)
One of the important assets owned by the organization cannot be separated from the performance of employees. To get a good performance then need to be given motivation to employees. A good leader will certainly create a comfortable environment and motivate employees with the aim that the spirit to work and provide maximum performance. Work motivation is an important factor to achieve good performance. For knowing influence of work motivation on employee performance at Dinas Kependudukan dan Pencatatan Sipil Kota Depok authors use quantitative research by doing methods of observation, interview questionnaires and study documentation . The author distributes questionnaires to 40 respondents then the authors process the data by using the formula calculation manually and SPSS version 20. Based on the calculation of product moment correlation coefficient obtained results of 0.750 where the number of scores indicates the strength of the relationship between motivation on employee performance. From the calculation of the coefficient of determination can be seen that the work motivation affect employee performance of 56.2 and seen from the regression equation formed Y 9.552 0.770X this shows that there is a positive and unidirectional influence between work motivation on employee performance.Keywords: Work Motivation, Performance Employees